Determinasi Faktor Kunci yang Memengaruhi Keberlanjutan Pertanian Kentang Sebagai Dasar Pengembangan Teknologi Smart Farming Berbasis Internet of Things (IoT) - Nainggolan, Mai Fernando; Sitohang, Maryanti; Setiawan, Perdi; Djuliansah, Dedi; Suardi, Tennisya Febriyanti (Universitas Galuh, 2026)
Potato farming is a strategic horticultural commodity that plays a vital role in the local economy and food security. However, the sustainability of potato production systems faces various challenges, including climate variability, input inefficiency, and low adoption of cultivation technologies. This study aims to identify key factors influencing the sustainability of potato farming as a basis for designing Internet of Things (IoT)-based Smart Farming technology. The analysis was conducted using the Matrix of Impacts Croisés-Multiplication Appliquée à un Classement (MICMAC) method on 15 variables representing the reinforcing dimensions, human resources, markets, and the environment. Data were collected through surveys, in-depth interviews, and Focus Group Discussions (FGDs) with potato farmers in Simalungun Regency. The results of the Matrix of Direct Influence (MDI) analysis indicate that Market Expansion, Education Level, and Price are determinant variables with high influence and low dependency. Meanwhile, Technology, Experience or training certification, and Farmer Development are included in the category of key variables with high influence and dependency, thus becoming strategic factors in the development of Smart Farming. Based on the Matrix of Indirect Influence (MII), the variables Technology, Farmer Education, Price, Experience, and Market Expansion have a strong indirect influence on the system. This finding confirms that effective IoT technology design must consider the interacting technical and socio-economic factors in potato farming systems. This research provides a scientific basis for strengthening the digital transformation of agriculture and formulating more adaptive and sustainable innovation policies.